Pengembangan Bahan Ajar Bahasa Indonesia Melalui Cerita Islami di MIN Beji Pasuruan - Saipul Hadi; Eka Misminarti (Al-Mudarris, 2020)
Efforts to help students and teachers in the Indonesian language learning process are by developing teaching materials through Islamic stories. This study aims to describe specifically the products made, in the form of Indonesian language teaching materials through Islamic stories for the fourth grade thematic at MIN Beji Pasuruan, as well as to see the differences in the learning outcomes of students who use and not the teaching materials. This type of research is in the form of research & development taking the theory of the Dick & Carey model. The research form is descriptive with a combination of qualitative and quantitative data analysis. The qualitative approach is validated by material experts, media experts, Indonesian language learning experts / classroom teachers, and students, and the quantitative approach uses the T test formula and uses SPSS computer calculations. The results showed that textbook products met valid criteria: the level of validity reached 95% for material expert tests, 96% for design experts, 98% for Indonesian language learning experts. Tested in small groups and the results reached 94% and 95%. He learning outcomes also showed an increase effectively by looking at the mean score of the experimental class 92 and from the control class 76.  In the T test using a correlation t-test formula with a confidence level of 95%, the results of t count ≥ t table are 5.44 ≥ 2.14, meaning that Ho is rejected and Ha is accepted. So that there are significant differences in the development of textbooks.